Why are Asian Economies Competitive? Example of Japan and China - Żukrowska, Katarzyna (Dlaczego gospodarki Azji są konkurencyjne? Przykład Japonii i Chin, 2011)
The article presents the results of evaluation of the competitiveness of the two economies: Japanese and Chinese, giving a list of common elements and differences deciding about the competitiveness of the two economies. It indicates which points are weak and which are strong in both cases, pointing at areas which decide that in case of the analysis of both economies there are long lasting potentials for keeping or increasing the position on international ranking lists. Both economies are considered to be open in limited way to trade and FDI inflows.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 192, s. 11-22
Keywords: stage of development; driving factors; competitiveness; current account; accumulation of reserves